The Belt and Road Initiative: Opportunities and Challenges for Nepal’s Development - Sapkota, Khila Nath; Nagarkoti , Payal (Humanities and Social Sciences Journal, 2024)
The Belt and Road Initiative (BRI) stands as a transformative global infrastructure project, reshaping international cooperation and connectivity. This study critically examines the opportunities and challenges BRI presents for Nepal’s development, emphasizing its potential impact and prospects for regional integration. Employing a descriptive research design, the study draws insights from qualitative data sourced from reputable secondary materials, including journal articles, government documents, and online resources. The strategic location of Nepal, sharing a 1,414 km Himalayan border with China, positions it as a vital link in regional trade and economic exchange. The BRI offers Nepal unprecedented opportunities to enhance connectivity, paving the way for its transformation into a transit hub between China and India. Key sectors such as trade, tourism, investment, and cultural exchange are self-assured to benefit, with railway connectivity emerging as a game-changer. Despite its immense potential, the BRI also brings significant challenges, including uncertainties around project feasibility, investment allocation, and security concerns. To fully leverage the initiative, Nepal must adopt a strategic approach to navigate these complexities, ensuring maximum developmental gains while fostering sustainable growth and regional collaboration. This study underscores the critical need for Nepal to seize the BRI’s opportunities while addressing its challenges to secure long-term economic transformation and global relevance.